PENGARUH MEDIA KOMUNIKASI DIGITAL LINE TERHADAP KUALITAS KOMUNIKASI INTERPERSONAL PADA MASA PANDEMI COVID-19 (Survei pada Pengguna Line Usia 15-25 Tahun) - Nindya Amelia (2023)
Since the enactment of the PSBB to stop the spread of Covid-19 in Indonesia, the process of communication activities has undergone many changes, the communication process which was previously carried out by meeting physically has changed to using intermediary media without meeting in person. Line is an application for exchanging messages that can be accessed using the internet network. This application, which is dominated by young people, was officially launched in Indonesia on June 23, 2011. The quality of communication produced through digital media is of course different from the quality of direct or face-toface communication. This is because the quality of communication is influenced by the effectiveness of sending and receiving messages, by communicating face to face we can get various nonverbal messages that we cannot get through online communication. This study aims to determine the influence of the use of digital communication media Line on the quality of interpersonal communication during the Covid-19 pandemic among Line users aged 15-25 years. This study uses associative quantitative methods with purposive sampling technique, with a total sample of 100 respondents and the analysis technique used is Pearson product moment correlation test, linear regression test, coefficient of determination test and hypothesis testing using the t test. The results of this study indicate that communication with digital media Line has a fairly strong relationship of 50% but the influence is insignificant or low, namely 25.1%, on the quality of interpersonal communication in the z generation, namely ages 15-25 years. In communicating through the digital media Line, participants can still show and feel the other party they are talking to, participants also try to read the message thoroughly and understand the contents of the message conveyed by the other person before giving a response. But even so, the results of the research that has been conducted show that the majority of participants do not agree to choose to speak through Line if they want to resolve conflicts.